Understanding and Tuning the Electrical Conductivity of Activated Carbon: A State-of-the-Art Review - Barroso Bogeat, Adrián (Critical reviews in solid state and materials sciences, 2021)
During the last decades, there has been a growing interest and research activity in the use of activated carbon (AC) and related materials as electrodes in electrochemical energy conversion and storage devices, like fuel cells, supercapacitors, and lithium-ion batteries. Among other factors, electrical properties, and especially conductivity, are well-known to play a pivotal role on the performance of ACs in these devices. Furthermore, other novel applications of AC-based materials, such as in electroadsorption, electrocatalysis, sensors and actuators, and so on, also rely heavily on their unique electrical properties. Therefore, the knowledge, understanding, and rationalization of these properties are essential with a view to assessing many of the current and future technological applications of ACs. The present paper critically reviews the available literature, including the latest published reports, on the electrical conductivity of AC. The accurate measurement of this property for ACs is rather difficult and requires the application of low to moderate compression to ensure the electrical contact. Estimated conductivity values are the result of a complex combination between a number of factors, among which the intrinsic conductivity of the single particles, their degree of contact and packing should be highlighted. Intrinsic conductivity is mainly determined by the texture, surface chemistry, and graphitization degree of AC, which strongly depend on the feedstock and the preparation method. Thus, the influence of these factors on the electrical conductivity of the resulting ACs is examined. Moreover, the influence of different adsorbed chemical species, mainly oxygen and water, is also dealt with. On the other hand, special emphasis is paid to the temperature dependence of conductivity, as its analysis is a powerful tool to gain insight into the electronic band structure and electron conduction process in carbon materials. In this regard, the different proposed mechanisms for electrical conduction in AC are exposed and compared.